Revolutionizing Housing Stock Management: Overcoming Challenges and Improving Services: Revolusi Manajemen Stok Perumahan: Mengatasi Tantangan dan Meningkatkan Layanan. - Kholmurodov Rachmatilla (Universitas Muhammadiyah Sidoarjo, 2023)
This scientific article examines the challenges faced by housing stock management companies in developing organizational and economic mechanisms, and proposes solutions to address them in the context of market relations. The study explores the management practices of these companies, analyzes the status of their services, and identifies opportunities to increase the range of services and improve their assessment. The research was conducted using a qualitative approach, drawing on interviews with industry experts and a review of relevant literature. The findings of this study provide valuable insights for policymakers, practitioners, and researchers seeking to enhance the effectiveness of housing stock management companies and improve the quality of housing services. The implications of the study suggest that future research should explore additional strategies for addressing the challenges faced by these companies, and for promoting sustainable development of the housing sector.Highlights: The article focuses on the challenges faced by housing stock management companies in developing organizational and economic mechanisms. The study explores the status of services provided by these companies and opportunities to improve them. The research provides valuable insights for policymakers, practitioners, and researchers seeking to enhance the effectiveness of housing stock management companies and improve the quality of housing services. Keywords: Housing stock management, organizational mechanisms, economic mechanisms, service improvement, market relations.